2004
DOI: 10.2298/hel0441075y
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis of some yield characters of sunflower, Helianthus annuus L

Abstract: The experiments comprising 25 sunflower hybrids were conducted in three locations in 2000 and 2001. These hybrids were evaluated for combining ability of 6 important yield components. Based on observations in this research, the average flowering duration of the hybrids ranged from 69.6 to 71.8 days, physiological maturity from 98.7 to 104.2 days, hectoliter weight from 355.2 to 408.5 g, 1000-seed weight from 32.5 to 43.5 g, plant height from 98.3 to 134.3 cm and head diameter from 12.6 to 14.0 cm. Based on all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 3 publications
4
8
0
1
Order By: Relevance
“…The importance of hybrid cultivars in sunflower has increased recently because of their higher seed yield compared with cross-pollinated varieties in many countries in the world. Hybrids of sunflower are more stable, highly self-fertile, with high yield performance, and more uniform at maturity (Kaya and Atakisi, 2004;Seetharam, 1979;Sujatha et al,2002). Resistance to diseases and Orobanche has also increased the importance of hybrid varieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of hybrid cultivars in sunflower has increased recently because of their higher seed yield compared with cross-pollinated varieties in many countries in the world. Hybrids of sunflower are more stable, highly self-fertile, with high yield performance, and more uniform at maturity (Kaya and Atakisi, 2004;Seetharam, 1979;Sujatha et al,2002). Resistance to diseases and Orobanche has also increased the importance of hybrid varieties.…”
Section: Introductionmentioning
confidence: 99%
“…The heterotic performance of a hybrid combination depends upon the combining abilities of its parents (Allard, 1960;Kadkol et al, 1984). Kaya and Atakisi (2004) reported that superior hybrids have been obtained by crossing cytoplasmic male sterile inbred (CMS) female and restorer lines with high general combining ability (GCA) and specific combining ability (SCA) values. General combining ability refers to the average performance of parental lines as reflected in its hybrid combinations and specific combining ability refers to the average performance of a particular cross.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, The female parents (lines) had a large proportion in the expression of traits than male parents also affirms the role of cytoplasmic and nuclear interactions in the expression of these traits. This also shows the importance of plant material diversity used for similar studies [53]. Similarly, significant GCA effect for seed yield was stated in the previous studies in that parent which were good general combiners for economic traits might be extensively used in hybridization programs to identify suitable parents for hybridization and developing potential hybrids for seed yield [54,55].…”
Section: Discussionmentioning
confidence: 53%
“…En los casos donde el efecto de ACG fue mayor al de ACE es recomendable hacer selección de genotipos con dichas cualidades y utilizar al menos a uno de ellos como progenitor en programas de cruzas simples, ya que según Reyes et al (2004), una cruza simple con al menos uno de sus progenitores con alta ACG puede garantizar altos valores en el rasgo evaluado. Valores significativos de ACG en componentes de rendimiento también han sido reportados para gerbera (Harding et al, 1981b) y otros cultivos como girasol (Helianthus annuus L.) (Kaya y Atakisi, 2004;Machikowa et al, 2011), tomate de cáscara (Physalis ixocarpa Brot.) (Camposeco et al, 2015), chile (Capsicum sp.)…”
Section: Resultados Y Discusiónunclassified